2022
DOI: 10.26534/kimika.v33i2.21-33
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Representations in Online General Chemistry Class: Promoting Chemical Understanding during the Covid-19 Pandemic

Abegail Joyce Opona,
Joje Mar Sanchez,
Kim Bondoc

Abstract: Teaching and learning in chemistry have been shifted to online classes due to the pandemic. With this, researchers investigated the use of multiple representations embedded to determine its effectiveness in online learning setup. A pretest-posttest with control quasi-experimental design was employed to two groups of Grade 11 STEM students taking up a general chemistry course in a private secondary institution in Cebu City, Philippines. The control group (n=30) was exposed to typical online class while the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The increased performances of the Control Group and Experimental Group A showed that traditional methods of teaching chemistry are applicable. Having hands-on laboratory activities allows the students to experience learning, which makes it a good option for learning Chemistry, as observed in recent literature on chemistry education (e.g., Sanchez, 2017Sanchez, , 2018Sanchez, , 2021Opona et al, 2022). The posttest performance of Experimental Group B is commendable because it showed that in the absence of lectures and physical labs, students could self-learn through videos.…”
Section: Comparison Of Pretest and Posttest Performancesmentioning
confidence: 82%
See 1 more Smart Citation
“…The increased performances of the Control Group and Experimental Group A showed that traditional methods of teaching chemistry are applicable. Having hands-on laboratory activities allows the students to experience learning, which makes it a good option for learning Chemistry, as observed in recent literature on chemistry education (e.g., Sanchez, 2017Sanchez, , 2018Sanchez, , 2021Opona et al, 2022). The posttest performance of Experimental Group B is commendable because it showed that in the absence of lectures and physical labs, students could self-learn through videos.…”
Section: Comparison Of Pretest and Posttest Performancesmentioning
confidence: 82%
“…Learning the concept of chemical changes drives us to see other evidence of chemical reactions. Chemistry teachers for this cause make use of different teaching styles to deliver this topic in their classes, such as ICT-supported strategy (Seibert et al, 2019), online experimentation (Babinčáková & Bernard, 2020), experiment method and computer simulations (Zendler & Greiner, 2020), and online multiple representations (Opona et al, 2022). With the advent of new technologies and in response to the limitations that the present health crisis brings about, teachers seek to adapt various techniques for students to be able to take hold and deepen their knowledge about pieces of evidence for chemical reactions.…”
Section: Introductionmentioning
confidence: 99%